(3fRgI Cgd GdMQejf aj YeGQI GdeTgOjfs - (3GdYGedj GdCUagGfj GdcGXej, CHh eMeO, MSf GdUOQ, MSf Hf gGOj Hf eMeO Ydj, J (B1354(3g`s ((3eTgO CejQ GdeDefjf Ydj Hf CHj WGdHs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3abO SCdJ COGe Gddg JCjjOc hJSOjOc Yf JbOe YeGQI Cj GdeTgOjf YeGQI eTgO SjOfG CHj YHO Gddg GdMSjf (B.. (3Ce YeGQI eTgO CejQ GdeDefjf Ydj (B..s
(3BNQgG (B:s
... (3hcGf jSei Pdc GdHMQ HMQ fj Ke La HYO Pdc abjd fj La aSejf HfLja Ke UGQ HYO Pdc jSehfg fLa dGfg cGf CNa Ydi CdSfJge (B.(3GfJgis
(3efShNI Yf fSNI efShNI Yf fSNI efShNI Yf fSNI HNW GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\224s
(3GdPQjYI (B24 - 71 ( 592)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJGQjNs